2015
DOI: 10.15244/pjoes/31226
|View full text |Cite
|
Sign up to set email alerts
|

Road Traffic Noise Exposure in the City of Novi Sad: Trend Analysis and Possible Solutions

Abstract: This paper evaluated exposure to road traffic noise in the city of Novi Sad, the second largest city in the Republic of Serbia. It has been investigated using analysis and systematization of the results on noise intensity in the city of Novi Sad, whether this parameter is within the approved limits for noise intensity during the day and night and whether it is in accordance with provisions of national norms of permissible noise levels in the environment, that is whether this parameter endangers people or not. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…To assess how well the ANN models are performing in terms of precision, the criterion used is the root mean square error (RMSE). The RMSE is calculated using the following equation [16]: (3) where O i is the observed value and P i is the computational value. The n parameter represent the number of data.…”
Section: Geographic Information Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess how well the ANN models are performing in terms of precision, the criterion used is the root mean square error (RMSE). The RMSE is calculated using the following equation [16]: (3) where O i is the observed value and P i is the computational value. The n parameter represent the number of data.…”
Section: Geographic Information Systemmentioning
confidence: 99%
“…However, according to Fallah-Shorshani et al [2] in recent years the issue of noise caused by traffic is becoming increasingly concerning. Because of that it requires a comprehensive and coordinated effort from all stakeholders to effectively address it and achieve the desired outcome of acceptable noise levels in different areas of the city [3]. Also, it should be noted that ambient noise and air pollution frequently appear together since they stem from identical origins, namely traffic [4], which is even more concerning because previous studies confirmed spatial connection between noise caused by traffic and air pollution [5].…”
Section: Introductionmentioning
confidence: 99%
“…In case the traffic situation warrants the selection of an option that generates more traffic noise, appropriate noise management strategies should be considered. For instance, introducing noise-reducing vegetation zones near intersections, installing noise barriers, and diverting traffic from heavily congested road networks are some recommendations that can be adopted by public agencies (47)(48)(49). Also, sustainable urbanization strategies such as controlling vehicle usage by creating environmental awareness, encouraging the use of more sustainable means of transport such as public transit, specifying traffic noise guidelines for roadway design, planning land use for noise-sensitive areas, and awareness campaigns need to be implemented by governments, public agencies, policymakers, and urban planners to reduce excessive traffic noise levels in urban areas (50,51).…”
Section: Future Work and Recommendationsmentioning
confidence: 99%
“…7 Tire recycling is also a social problem. 8,9 Tire separation technology and tire reuse are still very difficult. As some of the tires are environmentally hazardous, procedures need to be developed to eliminate this risk.…”
Section: Introductionmentioning
confidence: 99%